Características microbiológicas, físico-químicas e sensoriais do leite de cabra submetido à pasteurização e ao congelamento comercializados em Alfenas - Souza, Alan Kardec de (2012)
Goat's milk is a complete food, rich in proteins, fats, vitamins and minerals. Having very small lipid molecules, it is highly digestible when compared to other types of milk. One of the great challenges for the popularization of goat milk is that many potential consumers reject it because of its odor, flavor and high price when compared to pasteurized cow milk. This study aimed at analyzing the quality of the milk commercialized in Alfenas, MG, Brazil and evaluating the effect of pasteurization and freezing on its microbiological, physico-chemical and sensory characteristics. During 270 days, 3 batches of raw, pasteurized, and pasteurized and frozen goat milk were analyzed. Each batch was assessed every 90 days. The data were submitted to ANOVA and the Tukey test. The results showed that the slow pasteurization was effective in improving the microbiological quality of the milk, while no change was found in freezing it for 90 days. The physico-chemical and sensory characteristics of the milk was not changed by pasteurization and 90-day freezing. It was concluded that the goat milk commercialized in Alfenas, MG, Both pasteurized and pasteurized and frozen, have microbiological, physico-chemical and sensory quality within the standards established by law.